Transtorno do estresse pós traumático em idosos : prevalência e padrões brasileiros nos cuidados primários - Mello, Elisa Fasolin (2014)
In 1900 , less than 1 % of the world population was older than 65 years, today rate exceeded 9.2% and it is believed that in 2050 the elderly are one fifth of that population. The prevalence data for mental disorders in older people vary widely , but a conservative estimate is that 25 % have significant psychiatric symptoms . The number of elderly mentally ill is estimated at about 9 million in 2000 . The expectation is that this number will increase to 20 million by mid- secular . The post-traumatic stress disorder is a psychiatric disease that has been increasing in recent years. This condition may worsen disability associated with physical diseases and cognitive disorders , increase health care costs and mortality . The aim of this study was to evaluate the prevalence of post traumatic stress disorder in a random sample of elderly served by the Family Health Program in Porto Alegre . The study is crosssectional with prospective data collection . The sample consisted of 576 elderly randomly selected 30 teams of the Family Health of the Municipality of Porto Alegre ( FHS / POA ) randomized stratified by District Management mode. For diagnoses, psychiatrists with experience in assessing elderly used the Brazilian version of the Mini International Neuropsychiatric Interview Plus 5.0.0 ( 5.0.0 MINI plus). Regarding the results : a total of 3.4 % ( n = 20 ) of the sample showed the elderly post traumatic stress disorder , 0.8 % ( n = 4 ) diagnosed after 41 years. Of this total , 2.3 % ( n = ) had more than one period of PTSD since the beginning of the case , 0.8 % ( n = 4 ) lasting up to 3 months , 4.9% ( n = 26 ) from 3 to 6 months and 4.9% ( n = 26 ) over 7 months duration . Among elderly patients with the disorder some significant associations may be highlighted : aged 60-69 years ( 4.8% , P = 0.046 ), separated marital status ( 7.5 %, P = 0.020 ) and the number of residents in home ( 5.5 %, P = 0.013 ) . In this study we noticed a high mental distress in these individuals could be identified and evaluated predictors through the analyzes. The findings of this study are disturbing , being necessary to be replicated in other localities and samples .